Safer and cheaper: an enhanced milestone-based return to play program after anterior cruciate ligament reconstruction in young athletes is cost-effective compared with stand-ard time-based return to play criteria - DeFrancesco, C. J.; Lebrun, D. G.; Molony, Jr, J. T.; Heath, M. R.; Fabricant, P. D. (The American Journal of Sports Medicine, 2020)
Background: Safe return to play (RTP) after anterior cruciate ligament (ACL) reconstruction is critical to patient satisfaction. Enhanced rehabilitation after ACL reconstruction with appropriate objective criteria for RTP may reduce the risk of subsequent injury. The cost-effectiveness of an enhanced RTP (eRTP) strategy relative to standard post-ACL reconstruction rehabilitation has not been investigated.